Candidate counterparts to the soft gamma-ray flare in the direction of LS i +61 303 - Muñoz Arjonilla, A. J. (2009)
Context. A short duration burst reminiscent of a soft gamma-ray repeater/anomalous X-ray pulsar behaviour was detected in the direction of LS I +61 303 by the Swift satellite. While the association with this well known gamma-ray binary is likely, a different origin cannot be excluded. Aims. We explore the error box of this unexpected flaring event and establish the radio, near-infrared and X-ray sources in our search for any peculiar alternative counterpart. Methods. We carried out a combined analysis of archive Very Large Array radio data of LS I +61 303 sensitive to both compact and extended emission. We also reanalysed previous near infrared observations with the 3.5 m telescope of the Centro Astronómico Hispano Alemn and X-ray observations with the Chandra satellite. Results. Our deep radio maps of the LS I +61 303 environment represent a significant advancement on previous work and 16 compact radio sources in the LS I +61 303 vicinity are detected. For some detections, we also identify near infrared and X-ray counterparts. Extended emission features in the field are also detected and confirmed. The possible connection of some of these sources with the observed flaring event is considered. Based on these data, we are unable to claim a clear association between the Swift-BAT flare and any of the sources reported here. However, this study represents the most sophisticated attempt to determine possible alternative counterparts other than LS I +61 303.